2021
DOI: 10.3102/0002831221999405
|View full text |Cite
|
Sign up to set email alerts
|

District-Level School Choice and Racial/Ethnic Test Score Gaps

Abstract: The rapid expansion of school choice is restructuring public education in the United States. This study examines associations between charter and magnet school enrollment, White-Black and White-Hispanic segregation, and test score gaps at the district level from 2009 to 2015 in third to eighth grade using the Stanford Education Data Archive and the U.S. Department of Education's Common Core of Data. Robust findings indicate that higher charter school enrollment is associated with larger White-Black test score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To date, empirical scholarship regarding the efficacy of school choice has been mixed [8][9][10][11][12]. Recent reviews and meta-analyses of the extant literature have suggested that, on average, school choice policies have small, positive impacts on educational attainment [13], academic achievement [5], and disciplinary issues [10].…”
Section: School Choice Efficacymentioning
confidence: 99%
“…To date, empirical scholarship regarding the efficacy of school choice has been mixed [8][9][10][11][12]. Recent reviews and meta-analyses of the extant literature have suggested that, on average, school choice policies have small, positive impacts on educational attainment [13], academic achievement [5], and disciplinary issues [10].…”
Section: School Choice Efficacymentioning
confidence: 99%
“…For example, Saw (2016) used TIMSS to document a rapid growth in achievement gaps by parental education in Malaysia, and Salmela-Aro and Chmielewski (2019) related educational policy changes to trends in SES achievement gaps over time in Finland. A related literature has focused on trends in race/ethnic achievement gaps and their relation to school segregation (see e.g., Blatt and Votruba-Drzal, 2021;Kuhfeld et al, 2021;Reardon et al, 2019Reardon et al, , 2022.…”
Section: Evidence On Socioeconomic Achievement Gaps and Trends Over Timementioning
confidence: 99%
“…As traditional school districts expand their school choice programs to be responsive to current market-based demands for 21st century workforce skills, it is imperative to examine how existing school choice programs are influencing student achievement, which could potentially determine their success in accessing and thriving in postsecondary opportunities. A need clearly exists to determine the extent to which these programs are effectively implemented, particularly given the preponderance of studies about charter schools and magnet programs (e.g., Archbald et al, 2018;Blatt & Votruba-Drzal, 2021;Berends, 2015;Kitmitto et al, 2016;Linkow, 2011;Ni & Arsen, 2011;Teasley et al, 2016).…”
Section: Statement Of the Problemmentioning
confidence: 99%